FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN DETEKSI DINI KANKER SERVIKS DENGAN METODE PAP SMEAR PADA KARYAWATI DI RUMAH SAKIT SEMEN PADANG TAHUN 2017 - Yepni Nensi - (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
reality where case number of cervix cancer still enough heights and most of cervix cancer casefound is in the form of continuation stadium. Inspection of this Pap Smear still manyexperiencing resistance one of them is from the angle of human resource. Purpose of thisresearch is to know factors relating to execution of detection early cervix cancer with methodPap Smear at workingwoman in hospital Semen Padang the year 2017.Research type applied is analytic descriptive with design cross sectional studyexecuted in hospital Semen Padang in August 2017. Population in this research is allworkingwoman RS Semen Padang which married. Entirety of workingwoman fulfilling thiscriterion is 58, all populations is made research subject. Data collecting in enquette in theform of primary data with data processing stages;steps edit, coding, entry, tabulating andcleaning. Analysis univariat is done with descriptive statistic in the form of distribuísifrequency and percentage, while analysing bivariate is done with test chi-square with level ofmeaning α = 0,05.Result of this research got 20,7% less knowledgeable workingwoman, 56,9%workingwoman acts negativity, 53,4% workingwoman has negative motivation, 60,3%workingwoman have never executed detection early cervix cancer with method Pap Smear,there is the relation of level of knowledge and motivation of workingwoman about execution ofdetection early cervix cancer with method Pap Smear, there is no relation between position ofworkingwoman about execution of detection early cervix cancer with method Pap Smear inhospital Semen Padang the year 2017.This research indicates that knowledge and motivation there is relationship withexecution of detection early cervix cancer with method pap smear, while position there is norelationship with execution of detection early cervix cancer with method pap smear. Expectedto health officer to be more defins inspection of menyebarluasan information about executionof detection early cervix cancer with method pap smear.